2012
DOI: 10.3390/molecules17078010
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Mangostin, a Micronutrient of Mangosteen Fruit, Induces Apoptosis in Human Colon Cancer Cells

Abstract: Recently colorectal cancer rates have increased rapidly in Taiwan. The treatment of colorectal cancer includes surgery, radiation therapy and chemotherapy. Mangosteen (Garcinia mangostana) is a famous Asian tropical fruit. γ-Mangostin is a xanthone derivative isolated from the fruit hull. In previous studies, we found evidence of anti-inflammatory and anti-brain tumor activities in γ-mangostin. In this study, we performed further studies to assess the apoptotic effects of γ-mangostin on colorectal adenocarcino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 31 publications
3
39
0
1
Order By: Relevance
“…Mitogen‐activated protein kinases (MAPKs) include ERKs, JNKs and p38 MAPKs pathways, which are involved in regulating a variety of cellular responses, including proliferation, migrtaion, invasion and apoptosis . There is accumulating evidence for an important role for the MAPKs pathway, but these findings are controversial and complicated and depend on the specific characteristics of several of cell types .…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen‐activated protein kinases (MAPKs) include ERKs, JNKs and p38 MAPKs pathways, which are involved in regulating a variety of cellular responses, including proliferation, migrtaion, invasion and apoptosis . There is accumulating evidence for an important role for the MAPKs pathway, but these findings are controversial and complicated and depend on the specific characteristics of several of cell types .…”
Section: Discussionmentioning
confidence: 99%
“…To date, γ-mangostin have been reported to induce apoptosis in human colon cancer cells [44] and has antagonistic effects which can be used in the treatment of inflammation, pain, and neuropsychiatric symptoms [45]. Mangosteen juice can promote health but need to be consumed together with fat-containing meal because the xanthones in mangosteen juice are absorbed when ingested along with a high-fat food [46].…”
Section: Discussionmentioning
confidence: 99%
“…On the other side, the radical EEGM can react with the radical CCl3 or CCl3OO to yield a neutral product. Previous in vitro study showed that -mangostin induced the intracellular peroxide [17]. Another study found that -mangostin significantly decreased the levels of GSH, and increased GPx activity [18].…”
Section: Discussionmentioning
confidence: 99%